Prognostic significance of calcium-related genes in lung adenocarcinoma and the role of TNNC1 in macrophage polarization and erlotinib resistance - Feng, Jian; Chen, Zhe; Wang, Gaoming; Yao, Yu; Min, Xuewen; Luo, Jing; Xie, Kai (Frontiers in Immunology, 2025)
BackgroundCalcium signaling is critical in tumorigenesis. This study analyzed the characteristics of a calcium-related prognostic genes (CRPGs) signature in lung adenocarcinoma (LUAD) for prognostic value and explored TNNC1 as a potential therapeutic target for erlotinib resistance.MethodsClinical and RNA sequencing data from LUAD patients were obtained from the TCGA and GEO databases. CRPGs were identified through univariate Cox and Kaplan-Meier survival analyses. Calcium-related subtypes were determined via unsupervised clustering. A prognostic signature was constructed and validated using external datasets. Differences in immune infiltration and potential mechanisms in LUAD were explored using seven algorithms. The relationship between signature genes, chemotherapy sensitivity, and potential targeted therapies was evaluated. Potential drug targets were identified using Mendelian randomization (MR) and phenome-wide association studies (PheWAS). The association between TNNC1, erlotinib resistance, and macrophage M2 polarization was investigated through in vitro experiments.ResultsThe study identified 33 CRPGs and four subtypes among LUAD patients. The prognostic signature, comprising nine CRPGs, accurately predicted 1-, 2-, and 3-year overall survival. TNNC1 was identified as a crucial tumor suppressor gene and potential drug target. Down-regulation of TNNC1 decreased the IC50 value of erlotinib in LUAD cells and inhibited macrophage M2 polarization.ConclusionThis study developed a reliable prognostic signature based on nine CRPGs for predicting LUAD patient outcomes. TNNC1 may enhance LUAD cell resistance to erlotinib through macrophage polarization to the M2 phenotype.